Fundamentals and photocatalysis of methylene blue dye using various nanocatalytic assemblies- a critical review. (20th May 2021) - Din, Muhammad Imran; Khalid, Rida; Najeeb, Jawayria; Hussain, Zaib
Abstract: Methylene blue (MB) is a carcinogenic pollutant widely known for its hazardous impacts on humans and marine life. Recently, the photocatalysis mediated degradation of MB has been widely reported as an advanced approach for the removal of this harmful dye from the aqueous mediums. Numerous scientists have documented the use of nanomaterials (NMs) based photocatalytic assemblies for the degradation of MB. This study highlights the fundamentals and factors involved in the degradation reaction of MB. Furthermore, the detailed kinetics and mechanistic description are also presented for providing essential insights into the light mediated reaction of MB. The vast academic literature is organized by classifying the NMs based photocatalysts based on the utilized stabilization mediums and the advantages/disadvantages of the peculiar stabilization mediums are also discussed for presenting the comparative analysis of the reported stabilization mediums for the preparation of photocatalysts. Future prospects are also discussed for further extending the advancement of scientific research in this field. Graphical abstract: Image 1